Alternatives to Sorbents and Heat Storage Materials for Heat Storage Sorption Air Intake - Liu Jinya; Wang Liwei; Wang Jiayun; Wang Ruzhu (Zhileng xuebao)
Alternatives to the sorbents and heat storage materials used for a heat storage sorption air intake driven by solar energy were examined in this study. These included thermal conductivity and the sorption kinetic performance of composite sorbents using expanded natural graphite treated with sulfuric acid (ENG-TSA) and activated carbon fiber (ACF) felt as porous host matrixes, and thermal conductivity and differential scanning calorimetry (DSC) test for the composite phase-change thermal energy storage materials, i.e., stearic acid (SA)/ENG-TSA. The results revealed that the best thermal conductivity of the composite sorbent ENG-TSA-LiCl was 5.67 W/(m?K), and the largest water uptake was 1.54 g/g. The sorption performance of the composite sorbent ACF-LiCl using a vacuum impregnation method was better than that when using the atmospheric impregnation method. The water uptake of the consolidated sorbent of ASLi40 was 1.59 g/g, which can be applied to mass production. ENG-TSA-SA was suitable for solar energy and other low-grade heat energy recovery applications, with a high radial thermal conductivity (22.2 W/(m?K)) and appropriate internal phase transition temperature (65.9–77.1 ℃). The addition of a heat reservoir significantly slowed down the decrease to the desorption temperature.